2018
DOI: 10.5582/ddt.2018.01080
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of combined treatment with ombitasvir-paritaprevir-ritonavir, sofosbuvir with or without ribavirin as salvage therapy for Egyptian HCV experienced patients: A single center study

Abstract: We aimed to investigate the efficacy and safety of combination of sofosbuvir with ombitasvir, paritaprevir, and ritonavir ± ribavirin as a retreatment option for experienced Egyptian patients who failed previous sofosbuvir, daclatasvir ± ribavirin therapy. A total of 75 treatment-experienced patients were allocated for the completion of their treatment period according to criteria formed by the national committee for control of viral hepatitis. The enrolled patients were followed up throughout treatment, at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Re‐treatment with PEG‐IFN/SOF in PEG‐IFN/RBV‐experienced patients showed a high probability of treatment failure 117 . In chronic HCV patients who failed an initial SOF‐based regimen, a salvage regimen composed of PrO + SOF/RBV achieved an SVR rate of 93.4% with the intention‐to‐treat and 100% on the per‐protocol analysis 118 …”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Re‐treatment with PEG‐IFN/SOF in PEG‐IFN/RBV‐experienced patients showed a high probability of treatment failure 117 . In chronic HCV patients who failed an initial SOF‐based regimen, a salvage regimen composed of PrO + SOF/RBV achieved an SVR rate of 93.4% with the intention‐to‐treat and 100% on the per‐protocol analysis 118 …”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…They reported that this was the lowest SVR-12 among their used treatment regimens. Another study by Ismail and Wadea 24 also reported an intention-to-treat SVR-12 of 93.4% 23 . Our study showed a higher SVR-12 for this regimen, up to 99.3% in patients who completed their 12-week treatment regimens and 96.16% in all patients who received it.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, the response rate to this regimen was 96.2%. So far, the SOF/DCV±RBV combination has proved an adequate efficacy (SVR-12 of 94% in cirrhotic patients and 90.4% in treatment-experienced patients) and safety for the treatment of naïve and experienced Egyptian patients with CHC 24 . El-Khayat et al 25 reported that the addition of RBV significantly increased SVR-12 rates.…”
Section: Discussionmentioning
confidence: 99%